PERENCANAAN DAN PERANCANGAN PENGEMBANGAN RUANG PENDIDIKAN JURUSAN BANGUNAN SMK NEGERI 1 PADANG BERDASARKAN STANDAR NASIONAL PENDIDIKAN - 228-233 , Kapten Harahap (Universitas Negeri Padang, 2013)
The purpose of this design is designing the development of SMKN 1 Padang buildings especially for Construction Department such as ground plan, front view, back view, left view, and right view so the vision and missions of the school can be carried out to achieve education purposes.The design scheme was started from data collection that is consisted of location data, school master plan, guest data, student quantity, teachers and school administrator. The design process is doing micro and macro analysis. The rooms that were developed based on the analysis are classroom, plumbing and sanitation practice room, stone and concrete practice room, and also log practice room. The development was done by considering the Peraturan Menteri Nasional No. 40 Tahun 2008 Tentang Sarana dan Prasarana Sekolah Menegah Kejuruan/ Madrasah Aliyah Kejuruan (SMA/ MAK) Key words : Perencanaan, perancangan, pengembangan ruang